Debate techniques and oral expression for elementary school students. José Carlos Mariátegui Educational Institution 6063, Lima - Choquichanca Lavado De Bravo , Maribel (2025)
This analysis of debate and verbal communication skills among fifth-grade students at Educational Institution No. 6063, José Carlos Mariátegui, in Villa María del Triunfo, seeks to identify the connection between these variables. Its main objective is to establish whether debate technique and verbal expression skills are related in fifth-grade students. This study was conducted with a basic quantitative approach and a non-experimental design, using a sample of 32 students in a correlational study. Assessment tools for both debate techniques and oral expression skills were used. The findings reveal very low positive activation, and the p-value of .001 suggests that the results are significant, leading to the rejection of the null hypothesis and the acceptance of the alternative hypothesis. There is a significant relationship, with a moderate score of 0.562 between the two variables, supporting the alternative hypothesis that debate techniques are significantly linked to the development of oral expression of fifth-grade students at Educational Institution No. 6063, José Carlos Mariátegui, in Villa María del Triunfo.